Detecting step changes in the performance of cross-directional control systems - Taylor, A; Duncan, S (Pulp and Paper Technical Association of Canada, 2004)
This paper illustrates a segmentation procedure developed for data from cross-directional (CD) control systems. The aim of the segmentation is to identify unknown step changes in time series that are formed from vector measurements, such as those that are routinely collected by CD control systems. These step changes can be related to real process events and as a result, the information gained from the change point analysis can be used to improve the process. Two examples are presented in which changes are detected in the output data from a system that is used to control CD variation in film thickness on a plastic film process. The understanding gained from this analysis was used to make a significant improvement to the quality of the output obtained in the system studied.